Deficiencies of international investment law: What chances for "critical lawyers" to civilize global value chains and/or to transform the status quo of the economic world order? - Friederike Diaby-Pentzlin (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2020)
Rules should be fair, no matter from which perspective (Rawls, 1999). Given that Justitia holds a balance, current international investment law is disturbingly onesided. It mainly sets out to protect property positions of foreign investors. According to mainstream legal thinking, imposing obligations on transnational corporations (TNC) is only possible by means of the gentle non-binding rules of corporate social responsibility (CSR). As will be documented here, international investment law today has become a body of law for enterprises with hardly any regard for people and planet putting the private gains of few above the common good of many. Conventional approaches to legal questions deal with legal dogmata by detaching the law from its economic and political context. However, since legal norms are the result of societal negotiations, critical jurists have a role in analysing the law and its implementation, given the prevailing social and economic backgrounds. They see more easily that private interests increasingly drive legal doctrines and that social or environmental needs are largely neglected in mainstream legal activities. In international relations, the political consensus of the states in the United Nations (UN) has now moved beyond the Millennium Development Goals and their ideology of rich countries helping the poor (for a critique see Amin, 2006) within the dominant asymmetrical, fossil-based production and consumption paradigms. Due to acknowledgment of the increasingly pressing environmental and social needs, since 2016 more comprehensive and universal UN Sustainable Development Goals now aim to "transform our world" (United Nations, 2019). In international investment law, such changes are still to come. African states and societies in particular are undergoing economic and social transformations towards a nowadays also questionable modernity, and within decades, a process that took centuries in Europe. There are no more rural areas spared from agricultural or mining investments. So particularly in Africa, critical jurists and scientists need to analyse and point out which legal rules and interpretations on the international, regional, national and local level really serve the interests of the population in Africa. (...)
Keywords: F53; F54; O18; 330